Biofilm formation, siderophore production, virulence-associated genes and genetic diversity of Yersinia enterocolitica from food - Özdemir, Fatma; Arslan, Seza (Journal of the Hellenic Veterinary Medical Society, 2022)
Yersinia enterocolitica is widely found in nature and foods including those implicated in foodborne infections. The ability of this organism to multiply at refrigeration temperatures in food products with a prolonged shelf-life renders it a potential health risk for consumers. Y. enterocolitica isolates from food were investigated for biofilm formation and siderophore production at different temperatures (12, 25 and 37 °C) using the microtiter plate and CAS agar plate methods, respectively. The isolates were also evaluated with PCR for the presence of virulence genes and rep-PCR for genetic diversity. Most of the isolates showed high capability to form biofilm at all temperatures after 24 and 48 h of incubation. The results at 12 and 25 °C (P < 0.05) as well as at 25 and 37 °C (P < 0.05) showed a statistically significant difference in quantification of biofilm formation after 24 h; however, no difference was observed between findings at 12 and 37 °C (P > 0.05). There was a significant difference at 12 and 37 °C (P < 0.05) as well as at 25 and 37 °C (P < 0.05) after 48 h of incubation; conversely, no significant difference was observed between 12 and 25 °C (P > 0.05). Strong biofilm-producing isolates at 12 °C were found to be more after 48 h than after 24 h of incubation. Siderophore production was observed in 83.3% and 100% of the isolates at 25 and 37 ºC, respectively. However, no isolate produced siderophores at 12 °C. Genes myfA, fepA, fepD, fes, hreP, tccC and ymoA were detected in 16.7%, 33.3%, 100%, 100%, 44.4%, 5.6%, and 33.3% of the isolates, respectively. The rep-PCR revealed a high level of genetic differentiation among the isolates. The results indicated that Y. enterocolitica from food may act as a potential pathogen producing biofilm and siderophore while carrying virulence-associated genes.